Stuck in the Colonial Past?: Perpetuating Racist, Environmental Myths of Kenya in a Swiss Zoo. Issue 2 (1st September 2021) - Sithole, Samantha S.; Fernandes, Marianna; Hymas, Olivier; Sharma, Kavita; Walters, Gretchen
Abstract: This contribution challenges representations of landscapes and communities within zoos in Europe that may amplify colonial narratives of local people through a racialised and often static lens. Instead of a holistic portrayal of the relationship between humans and nature that the EAZA (European Association of Zoos and Aquaria) stipulates within its guidelines, some European zoos continue to perpetuate a narrow view of foreign landscapes within their exhibits. Utilising the concept of representation, this short article argues that Zoo Zürich reinforces colonial narratives through its new Lewa exhibit, an exhibit based on a Kenyan conservancy. This piece is based on an improvised visit to the zoo to see the new African exhibit. It highlights discrepancies between the Lewa exhibit, guidelines of the EAZA and the Lewa Conservancy in Kenya. In this light, we propose recommendations for European zoos to decolonise their institutions and exhibits based on an understanding that is not only scientific, but also historical, critically reflective, and inclusive of non-Western perspectives.